2011
DOI: 10.1016/j.scico.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Formal specification of MPI 2.0: Case study in specifying a practical concurrent programming API

Abstract: a b s t r a c tWe describe the first formal specification of a non-trivial subset of MPI, the dominant communication API in high performance computing. Engineering a formal specification for a non-trivial concurrency API requires the right combination of rigor, executability, and traceability, while also serving as a smooth elaboration of a pre-existing informal specification. It also requires the modularization of reusable specification components to keep the length of the specification in check. Long-lived A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The main challenge, however, is to model involved APIs and system calls. One solution is to build light-weight models or abstract interpretations for these APIs as we did for MPI 2.0 [18].…”
Section: Assertion Checking (Functional Correctness)mentioning
confidence: 99%
“…The main challenge, however, is to model involved APIs and system calls. One solution is to build light-weight models or abstract interpretations for these APIs as we did for MPI 2.0 [18].…”
Section: Assertion Checking (Functional Correctness)mentioning
confidence: 99%
“…Instead, this decision is a natural consequence of exploiting the happens-before order we have defined for MPI [47]. While MPI itself can be formalized in several ways (e.g., [35,22]), we have found that it is this more "macroscopic" formal semantics of happens-before ordering that directly guides the construction of the ISP scheduler.…”
Section: Dynamic Analysis Of Mpimentioning
confidence: 99%